River training works using geotextiles / Muhammad Hisham Muhammad Said - Muhammad Said, Muhammad Hisham (1992)
In this project the use of geotextiles in river training works is dealth with. The objectives are ; first to outline the use of geotextiles in river training works. Secondly, to clearly define the geotextile; its definition, functions as well as its properties. Thirdly, to explain the concept of river training works. Fourthly, to discuss and provide the design, construction and maintenance criteria required and lastly to provide a case study of river training works using geotextiles. Emphasis is placed on the design, construction and maintenance criteria only.